The Development of Etnomathematics Teaching Materials Using Ume Kbubu Context on Students of Mathematics Education Department - Stanislaus Amsikan; Yohanis Ndapa Deda (International Journal of Trends in Mathematics Education Research, 2020)
This study aims to develop Teaching Materials in the form of Ethnomatematics student worksheets using the Ume Kbubu (traditional house in Timor-Indonesia) context for undergraduate students. It is a kind of research and development using the formative Tessmer Evaluation Model. It consisted of two stages of development, namely the preliminary analysis stage and the formative evaluation stage. The subjects of the current study were students who programed Ethnomatemics, academic year 2019/2020, at Mathematics Education Study Program, Universitas Timor- Indonesia. Data collection techniques applied were tests of learning outcomes, observation, and interviews. Experts have validated the development of product design (prototypes) of student worksheets, using the Ume Kbubu context. The results of the current research have shown that students worksheet meets the criteria of practicality and effectiveness. Thus, Ethnomatematics Teaching Material using the context of Ume Kbubu is stated as useable in the process of lecturing on Ethnomathematics courses, especially for undergraduate mathematics education study programs in Universitas Timor- Indonesia.